If x=3x+2 and y=2k-1 is a solution of the equation 4x-3y+1=0, find the value of k.
Answers
Correct question :
If x = 3k + 2 and y = 2k - 1 is a solution of the equation 4x - 3y + 1 = 0 , find the value of k.
Answer :
⟹ k = -2
Explanation :
Given :
- x = 3k + 2
- y = 2k - 1
- 4x - 3y + 1 = 0
According to the question :
In this case, we are substituting the values of ' x ' and ' y ' in the equation ' 4x - 3y + 1 = 0 '
Substituting values :
⇛4 ( 3k + 2 ) - 3 ( 2k - 1 ) + 1 = 0
⇛( 12k + 8 ) - ( 6k - 3 ) + 1 = 0
⇛( 12k - 6k ) - ( -3 - 8 ) + 1 = 0
⇛6k + 11 + 1 = 0
⇛6k + 12 = 0
⇛6k = 0 - 12
⇛6k = -12
⇛k = 6 / -12
⇛k = -2
» So, It's Done !! «
Answer :
›»› The value of k = -2
Given :
- x = 3k + 2
- y = 2k - 1
To Find :
- The value of k = ?
Required Solution :
Here in this question, we have to find the value of k So, firstly we have to Both given elements have to be considered as equation 1 and equation 2. And then we have to put the equation 1 and equation 2 into 4x - 3y + 1 = 0. Then, we can frame equation to get the result of x
x = 3k + 2 .....(1)
y = 2k -1 .....(2)
So let's start solving the equation and understand the steps to get our final result for x.
Putting the equation 1 and equation 2 into 4x - 3y + 1 = 0
⇛ 4x - 3y + 1 = 0
⇛ 4(3k + 2) - 3(2k - 1) + 1 = 0
Distribute 4 through the parentheses,
⇛ 12k + 8 - 3(2k -1) +1 = 0
Distribute -3 through the parentheses,
⇛ 12k + 8 - 6k + 3 + 1 = 0
Collect like terms,
⇛ 6k + 8 + 3 + 1 = 0
Calculate the sum of the positive numbers,
⇛ 6k + 12 = 0
Move constant to the right-hand side and change it's sign,
⇛ 6k = -12
Divide both sides of the equation 6,
⇛ k = -2
║Hence, the value of k is -2.║